2004
DOI: 10.1111/j.1365-2125.2004.02077.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of pyrimethamine and sulfadoxine in children with congenital toxoplasmosis

Abstract: AimsTo develop a population pharmacokinetic model for pyrimethamine (PYR) and sulfadoxine (SDX) in children with congenital toxoplasmosis. MethodsChildren were treated with PYR (1.25 mg kg -1 ) and SDX (25 mg kg -1 ) (Fansidar ® ) plus folinic acid (Lederfoline ® 5 mg). Plasma concentrations, available from a therapeutic drug monitoring database, were determined by high-per formance liquid chromatogrphy. Population pharmacokinetic analysis was performed using a nonlinear mixed effects model. ResultsEighty-nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 19 publications
3
28
2
2
Order By: Relevance
“…In particular, the median t 1/2␤ s of 18.8 and 9.9 days for pregnant and nonpregnant women, respectively, are higher than previously reported values, which have ranged from 2.9 to 5.1 days in adults (3,5,12,14,19,25,32,34,35) and from 2.8 to 4.5 days in children (3,9,30,38). Most other studies have utilized a single-compartment model (3,9,14,30,32) and/or sampling durations of Յ14 days (12,14,32,38). In one study that attempted to measure PYR concentrations to 42 days, 38% of plasma concentration data was excluded from analysis because levels were either undetectable or below the 10-g/liter LOQ of the LCMS assay (3).…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…In particular, the median t 1/2␤ s of 18.8 and 9.9 days for pregnant and nonpregnant women, respectively, are higher than previously reported values, which have ranged from 2.9 to 5.1 days in adults (3,5,12,14,19,25,32,34,35) and from 2.8 to 4.5 days in children (3,9,30,38). Most other studies have utilized a single-compartment model (3,9,14,30,32) and/or sampling durations of Յ14 days (12,14,32,38). In one study that attempted to measure PYR concentrations to 42 days, 38% of plasma concentration data was excluded from analysis because levels were either undetectable or below the 10-g/liter LOQ of the LCMS assay (3).…”
Section: Discussioncontrasting
confidence: 43%
“…In contrast to SDOX, the PK parameters for PYR in both our patient groups differed markedly from those found in a wide variety of clinical and ethnogeographic settings (3,5,9,11,12,14,19,21,25,30,32,34,35,38). In particular, the median t 1/2␤ s of 18.8 and 9.9 days for pregnant and nonpregnant women, respectively, are higher than previously reported values, which have ranged from 2.9 to 5.1 days in adults (3,5,12,14,19,25,32,34,35) and from 2.8 to 4.5 days in children (3,9,30,38). Most other studies have utilized a single-compartment model (3,9,14,30,32) and/or sampling durations of Յ14 days (12,14,32,38).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In addition, the relationship between in vitro susceptibility and clinical resistance remains to be examined. Pharmacokinetic studies have revealed marked individual variations in pyrimethamine concentrations in human immunodeficiency virus (HIV)-infected patients (20,49) and in children treated for congenital toxoplasmosis (11,33,44,47). In HIV-infected patients with toxoplasmic encephalitis, a positive relationship between clinical and radiological responses and median atovaquone plasma concentrations has been shown (46).…”
Section: Downloaded Frommentioning
confidence: 99%